Penerapan Metode MOORA Untuk Menentukan Serangan Hama Dan Penyakit Tanaman Kakao - Neni Mulyani; Jeperson Hutahaean; Jihan Aulia Putri Fahdrina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
− Lubuk Palas Village, precisely in the Banjar Village area, is one of the villages where most of the people make a living as farmers. One type of plantation crop that is cultivated in Lubuk Palas Village is cocoa. However, the productivity of cocoa plants is always decreasing, the problem is pests and diseases. So far, the farmers of Lubuk Palas Village are still using manual methods such as guessing in determining pests and diseases on the cocoa plant. This causes the results to be less accurate and take a long time to determine. Due to the absence of a system that can help farmers in Lubuk Palas Village in overcoming pest and disease attacks on cocoa plants quickly. Therefore, a decision support system is needed using the MOORA method with the calculation of the web-based MOORA method that can make it easier for cocoa farmers in Lubuk Palas Village to determine pest and disease attacks on cocoa plants quickly, and can overcome the losses caused by attacks by nuisance organisms. the cocoa plant. In this study using quantitative methods. The data sources used are based on interviews, questionnaires and observations. Based on the data analysis that has been carried out, it is concluded that fruit-sucking ladybugs (Helopeltis spp) are obtained with a weight value (0.42545616), and fruit rot disease (anthracnose) is obtained with a weight value (0.426163942), these pests and diseases often occur and detrimental to cocoa farmers in Lubuk Palas Village.